Green Building Rating Systems and Construction Waste in High Density Urban Environment: The Case Study of Hong Kong - Jaillon, Lara; Poon, Chi-Sun; Chan, Yan Yu; Lee, Ming Wai; Cai, Xiaolei (International Journal of Sustainable Construction Engineering and Technology, 2021)
Hong Kong, as many other countries, is currently facing a waste management crisis with the shortage of reclamation sites and landfill space. Examination of construction waste management (CWM) criteria within Hong Kong’s BEAM Plus is limited and lacking. In this paper, CWM criteria were assessed and a case study was conducted on a recent project, pursuing BEAM Plus, to assess the effectiveness of CWM criteria to facilitate waste reduction. The findings revealed that the overall impact of BEAM Plus on construction waste reduction is negligible. The case study showed that the reasons material/waste-related credits are not commonly attempted is due to the lack of minimum thresholds and a low weighting relative to credits in other categories. In the case study, waste generated per constructed floor area was 0.21 tons/m2. This paper also makes recommendations to improve CWM criteria in BEAM Plus in order to promote a more sustainable building industry.